1998
DOI: 10.1046/j.1365-2141.1998.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone replacement therapies on fibrinogen and plasma viscosity in postmenopausal women

Abstract: In women, cardiovascular morbidity and mortality sharply increase after the onset of menopause. There is substantial evidence that hormone replacement therapy (HRT) may decrease the risk of coronary heart disease (CHD); however, the mechanisms of this preventive effect are unclear. We investigated the association between HRT and plasma viscosity as well as fibrinogen levels in postmenopausal women of a population-based sample (n=300, age 52-65 years). A total of 94 women used HRT; of these, 50 took oestrogen m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 27 publications
3
13
0
1
Order By: Relevance
“…We found fibrinogen to be significantly lower among current HRT users than women who never used HRT for both diabetic and nondiabetic women. Similar findings were observed in a group of postmenopausal women aged 52-65 years (n ϭ 300), where HRT usage was associated with significantly lower fibrinogen concentration (232 vs. 268 mg/dl) and decreased plasma viscosity (29). Results from this study, however, were not provided separately for diabetic and nondiabetic women.…”
Section: Results -supporting
confidence: 76%
“…We found fibrinogen to be significantly lower among current HRT users than women who never used HRT for both diabetic and nondiabetic women. Similar findings were observed in a group of postmenopausal women aged 52-65 years (n ϭ 300), where HRT usage was associated with significantly lower fibrinogen concentration (232 vs. 268 mg/dl) and decreased plasma viscosity (29). Results from this study, however, were not provided separately for diabetic and nondiabetic women.…”
Section: Results -supporting
confidence: 76%
“…In other studies, however, exogenously administered hormones were shown not to affect the levels of F 1+2 [11,13] or thrombin-antithrombin (TAT) complex [13]. These and related studies [14][15][16][17] involved measurements of procoagulant or fibrinolytic factors after administration of HRT in different dosages and formulations, in case-control studies. None of these studies addressed any association between the actual circulating levels of oestrogenic hormone(s) and haemostatic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in postmenopausal women from the S1 we found decreased plasma viscosity values during hormonal replacement therapy [12].…”
Section: Plasma Viscositymentioning
confidence: 53%